Hubungan antara Pengetahuan dan Sikap Ibu dengan Upaya Pencegahan Gigitan Nyamuk Anopheles pada Balita - Septiana Fathonah, Purwanta, Putu Oka Yuli N (Fakultas Kedokteran Universitas Gadjah Mada, 2010)
Background: Malaria kills approximately 1 million children each year and also a major cause of illness, health care visited, and hospitalizations in part of the world. In children malaria will interfere growth and development. At 2007, in Kelurahan Hargotirto and Hargowilis, there were 22 cases of malaria of 94 cases of malaria found in Kabupaten Kulonprogo. The first line of defence against malaria infection is personal protection toward mosquito bites.Objective: This study analyzed the correlation between mother knowledges and attitudes in avoiding anopheline mosquito bites in Kelurahan Hargotirto and Hargowilis Kecamatan Kokap Kabupaten Kulonprogo.Method: This study was cross-sectional. Data collection method used questionnaire. Samples were gathered by combination between cluster and systematic random sampling.The sample size in this study was 87 people. The data were analyzed using univariate and bivariate analyses. Univariat analyses produced frequency distribution of respondents and describes dependent and independent variables. This study used Kolmogorov-Smirnov comparison test. Bivariate analysis used Rank Correlation Test (Spearman).Result: Bivariate analysis results show that knowledge has a significant correlation with avoiding anopheline mosquito bites behaviour (p<0,05). Education level and attitude do not have a significant correlation with avoiding mosquito bites behaviour (p>0,05). There is no correlation between previous history of malaria in children with mother behaviour in avoiding anopheline masquito bites in children under five years (p>0,05).Conclusion: Knowledge has a significant correlation with avoiding anopheline mosquito bites behaviourKeywords: Knowledge, attitude, avoiding anopheline masquitoes bites